Pengaruh Perputaran Modal Kerja, Perputaran Kas, Likuiditas, dan Pertumbuhan Laba terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Eka Fuji Lestari; Wahyumi Ekawanti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
The rapid development of the pharmaceutical industry in Indonesia presents both an opportunity and a challenge in increasing company value amidst the dynamics of an increasingly digital and competitive capital market. This phenomenon demonstrates that strong operational performance does not always translate into high market value, making it crucial to identify internal factors that influence company value, particularly in the pharmaceutical subsector, which plays a strategic role in Indonesia.This research aims to analyze the effect of Working Capital Turnover, Cash Turnover, Liquidity, and Profit Growth on Company Value in pharmaceutical companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The research method used was quantitative with an explanatory approach. The sampling technique used total sampling, with a sample size of 10 companies. Secondary data, in the form of financial statements, were analyzed using multiple linear regression analysis.The results indicate that only Cash Turnover significantly impacts company value, with a negative effect, while Working Capital Turnover, Liquidity, and Profit Growth do not. These findings suggest that efficient working capital management and consistent profit growth play a crucial role in increasing the value of pharmaceutical companies. This research is expected to be a reference for management in strategic decision making and for academics for further research.